FORMULASI DAN EVALUASI CROFFLE DARI DAUN KATUK (Sauropus androgynus L) DAN TEPUNG MOCAF SEBAGAI HEALTHY FOOD - Isronijaya, Mohamad (Berkala Ilmiah Mahasiswa Farmasi Indonesia, 2023)
Croffle stands for Croissant and Waffle, which is a food made from croissant dough cooked using a waffle maker. The purpose of this study was to determine the nutritional content and preference level of panelists for croffle formulated with katuk leaves. The first factor was the difference in the proportion of katuk leaves from the three concentrations, while the second factor was the difference in the proportion of MOCAF flour consisting of the three concentrations. Then each evaluation was carried out twice. The organoleptic data analysis used was the hedonic test with texture, shape, aroma and color test parameters. Further tests were carried out with Duncan's test. Proximate test was performed on all products. The croffle formulation that many panelists liked was the F0 sample, namely without the addition of katuk leaves. Meanwhile, from the evaluation that has been carried out, the sample that has good nutritional quality is F3, meaning that there is the addition of katuk leaves at a concentration of 10%. Based on the research results, katuk leaves and mocaf flour have a significant effect on the formula and assessment of croffle as a healthy food. The croffle formulation that many panelists liked was the F0 sample, which means without the addition of katuk leaves. Meanwhile, from the evaluation that has been carried out, the sample that has good nutritional quality is F3, meaning that there is the addition of katuk leaves at a concentration of 10%.